Conformastatic disk-haloes in Einstein-Maxwell gravity (2013)
We present a relativistic model describing a thin disk surrounded by a halo in the presence of an electromagnetic field. The model is obtained by solving the Einstein-Maxwell equations on a particular conformastatic spacetime background and by using the distributional approach for the energy-momentum tensor. A class of solutions is obtained in which the gravitational and electromagnetic potentials are completely determined by a harmonic function only. A particular solution is given that is asymptotically flat and singularity free, and satisfies all the energy conditions. © 2013 American Physical Society.